Pengembangan Masyarakat melalui Pendidikan Kajian Kitab Kuning: Studi Kitab Al-Iqtishod Al- Islami, Al Fiqh Al Islami Wa Adillatuhu, Tafsir Al- Qur'an, dan Ilmu Faraid dalam Program Friday Literacy - Rachmad, Dedy; Mustafa, Muhammad Isa; Afifi, Ahmad Levi Fachrul; Effendi, Erus (Tazkia Islamic University College, 2025)
Community service is a concept and practice in which individuals, groups, or institutions provide sustained positive contributions to society. The main goal of this service is to improve the quality of life for communities, address social issues, and support sustainable development. One tangible form of this service is through educational development via the Friday Literacy program. “Kitab kuning